Accreditation of Higher Education in Costa Rica: status of the Dentistry career (Revista Electrónica Calidad en la Educación Superior, 2021)
Higher education is one of the pillars of society, it guarantees a prosperous and competitive socioeconomic system. A university institution with high quality in its programs will achieve in the best way its mission to transform society. Accreditation is the process by a university degree certifies the quality of the education it provides. In Costa Rica, the Sistema Nacional de Acreditación de la Educación Superior (SINAES) is the entity in charge of accreditations and within its registries, three Dentistry Faculties have this recognition: at a public level, the Universidad de Costa Rica and at a private level the Universidad Latina de Costa Rica and the Universidad Latinoamericana de Ciencia y Tecnología.
Keywords: higher education; accreditation; dentistry; university